2019
DOI: 10.1021/acs.chemrestox.9b00407
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Lesions Arising from 5-(Uracilyl)methyl Peroxyl Radical Addition to Guanine: Product Analysis and Mechanistic Studies

Abstract: The reaction of hydroxyl radical (HO•) with thymine in DNA generates 5-(uracilyl)-methyl radicals (T•) and the corresponding methylperoxyl radical (TOO•) in the presence of O2, which in turn propagates damage by reacting with a vicinal nucleobase. This leads to so-called double or tandem lesions. Because methyl oxidation products of thymine are major products, we investigated the reactivity of TOO• using a photolabile precursor: 5-(phenyl­thio­methyl)­uracil (TSPh). The precursor was prepared and incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Tandem lesions containing N -formamide and 8oxoG have previously been characterized and detected in oligonucleotides and isolated DNA exposed to ionizing radiation and Fenton-like reactions implying the generation of hydroxyl radicals. ,,,, The mechanism of formation of these and other tandem lesions has been proposed to involve initial attack of • OH and incorporation of oxygen to form peroxyl radicals, which subsequently react with the adjacent G moiety to form either 8oxoG or 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyG). , A similar mechanism may be responsible for the formation of tandem lesions by ozone. In addition to the reaction pathway involving a bipolar carbonyl intermediate (analogous to I → II ), Pryor proposed O–O bond homolysis of the initial ozonide into a biradical species to explain the effects of temperature, metal chelators, and H 2 O on the formation of radical species during ozone-mediated oxidation of a biological target .…”
Section: Discussionmentioning
confidence: 99%
“…Tandem lesions containing N -formamide and 8oxoG have previously been characterized and detected in oligonucleotides and isolated DNA exposed to ionizing radiation and Fenton-like reactions implying the generation of hydroxyl radicals. ,,,, The mechanism of formation of these and other tandem lesions has been proposed to involve initial attack of • OH and incorporation of oxygen to form peroxyl radicals, which subsequently react with the adjacent G moiety to form either 8oxoG or 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyG). , A similar mechanism may be responsible for the formation of tandem lesions by ozone. In addition to the reaction pathway involving a bipolar carbonyl intermediate (analogous to I → II ), Pryor proposed O–O bond homolysis of the initial ozonide into a biradical species to explain the effects of temperature, metal chelators, and H 2 O on the formation of radical species during ozone-mediated oxidation of a biological target .…”
Section: Discussionmentioning
confidence: 99%
“…We can therefore conjecture that in cells, the initial radicals that produced this type of CLs (143) would also be effective in crosslinking DNA with proteins. Moreover, it has been demonstrated that a single radical, such as thymine radical, could produce tandem lesions and protein‐DNA crosslinks (151,152). As shown in Fig.…”
Section: Can 0–3 Ev Electrons Produce Lethal Dna Damage?mentioning
confidence: 99%
“…Tandem base modifications have also been reported; they are induced following the initial formation of peroxyl pyrimidine radicals that subsequently react with vicinal bases . Under UHV, such reactions would not occur, but we cannot rule out the possibility of reaction with oxygen, during the sample analysis procedure under atmospheric conditions. , …”
mentioning
confidence: 91%
“…30 Under UHV, such reactions would not occur, but we cannot rule out the possibility of reaction with oxygen, during the sample analysis procedure under atmospheric conditions. 70,71 Much of our present understanding on the production of cluster lesions has revolved around the concept of random multiple hits by the primary particles and radiation-generated species along tracks, causing two or more simple lesions within 20 bp. This concept was introduced and emphasized by Ward, 72,73 Goodhead, 74,75 and others.…”
mentioning
confidence: 99%